DEVELOPMENT OF STUDENT WORKSHEET BASED ON SCIENTIFIC APPROACH IN ENGLISH LEARNING AT SMA N 2 KOTA BENGKULU - Elva Utami; Lisa Rakhmanina (Language and Education Journal, 2019)
The objective of this study was to produce student worksheet which is valid based on scientific approach. Research and development design was used for this study. The research was conducted at Tenth Grade Students of SMAN 2 Kota Bengkulu. Data collecting techniques used were student worksheet validation and lesson plan validation. The Data were analyzed using descriptive analysis of quantitative and qualitative. Based on the results of an assessment 93% of all student worksheets components were valid and lesson plan developed from all components were also valid with 80% reliability. It can be concluded that student worksheets developed by researchers is in the feasible category